SU‐E‐I‐74: Quantitative Instrumentation for Subject Workload From Exercise During 31‐Phosphorus MR Spectroscopy to Monitor Phosophocreatine Recovery as An Index for Mitochondrial Metabolism - Settles, F; Clarke, G (Medical physics (Lancaster), 2014)
Purpose: Measurement of mitochondrial function is relevant to aging and diabetes. Phosphorus‐31 magnetic resonance spectroscopy (31P‐MRS) can be used to evaluate the rate of phosphocreatine (PCr) recovery following exercise. The project's aim is to develop a reproducible measurement technique using an exercise apparatus to quantify PCr recovery in the vastus lateralis muscle (VL). A workload instrument was developed to quantify work output of each subject. Methods: An apparatus was designed to exercise the VL with subjects in the prone position with an 1H‐31P surface coil against the thigh. Since subjects exercise at different rates and intensities, a strain gage instrument was developed to quantify the amount of work done. During a 5 minute exercise period, PCr depletion levels were measured using MRS. Coincidentally, the force exerted on the articulating arm of the apparatus appears as a voltage from the instrument on a strip recorder sampling at 1 mS and is captured as numerical values. Results: The exercise apparatus is a compact, single‐piece PVC assembly with little mass (<3 kg), and provides resistance of up to 13.5 kg within the confines of the bore. The instrument outputs a voltage relative to the force applied against the resistance. A subject's performance and level of fatigue is visualized in real time and captured for post processing. The summation of force applied (strain level) vs. time is the work output. Brisk exercise produced a rapid drop in PCr and concomitant increase in inorganic phosphate. Conclusion: The exercise apparatus immobilizes the thigh and surface coil during dynamic flexion exercise and recovery phases of the protocol. Spectral data acquired demonstrated PCr depletion and recovery in VL correlated to the subject workload.Clinical Relevance/Application:Noninvasive, reproducible measures of mitochondrial function by a well‐characterized in‐vivo biomarker can provide insights for the characterization and treatment of metabolic diseases.